Performance Assessment and Improvement of a Three-Legged Intersection at New Plaza, Kathmandu - Amgain, Arbin; Silwal, Satkrit; Shrestha, Sanjaya; Poudel, Aayush; Luitel, Suyash; Pokhrel, Asmita (Journal of UTEC Engineering Management, 2025)
New Plaza Intersection, located in Anamnagar, is a three-legged intersection that suffers from severe congestion during the peak hours. This place consists of a number of educational institutions, banks, consultancies, offices and commercial buildings. So, there is a high volume of traffic movement in this area but the road capacity is very low in comparison causing traffic congestion. A video-graphic survey was carried out for three weekdays to collect the traffic data. The traffic volume count was done through manual counting method and using the PCU values of NRS 2070. The peak hour traffic volume during the morning peak hours was much higher in compariso evening peak hours with motorcycles and scooters constituting 78% of the total traffic. SIDRA Intersection 8.0 software was used for the development of the simulation model of the intersection. The models were calibrated and validated for saturation flow rate and back of queue (BOQ). From the analysis of the study, the LOS of the intersection was found to be F which indicates breakdown of flow, extreme delays and long queue length. The existing traffic signals in the intersection were found to be not properly utilized. So, to tackle the problems of congestion, optimal signal timing was used. Although there was no improvement in the level of service (LOS) of the intersection, the use of optimum cycle length resulted in a decrease of average delay and queue length in the intersection.